Guanxinning Tablet Alleviates Post-Ischemic Stroke Injury Via Regulating Complement and Coagulation Cascades Pathway and Inflammatory Network Mobilization - Wang Y; Li Y; Zhou Y; Gao Y; Zhao L (Dove Medical Press, 2024)
Yule Wang,1 Yiran Li,2 Yue Zhou,2 Yue Gao,1 Lu Zhao2 1Zhejiang Key Laboratory of Traditional Chinese Medicine for the Prevention and Treatment of Senile Chronic Diseases, Department of Geriatrics, Affiliated Hangzhou First People's Hospital, School of Medicine, Westlake University, Hangzhou, People's Republic of China; 2Pharmaceutical Informatics Institute, College of Pharmaceutical Sciences, Zhejiang University, Hangzhou, People's Republic of ChinaCorrespondence: Lu Zhao; Yue Gao, Email lzhao@zju.edu.cn; gaoyue@hospital.westlake.edu.cnBackground: Currently, ischemic stroke (IS) continues to significantly contribute to functional deterioration and reduced life quality. Regrettably, the choice of neuro-rehabilitation interventions to enhance post-IS outcomes is limited. Guanxinning tablet (GXNT), a multi-component medicine composed of Danshen and Chuanxiong, has demonstrated neuroprotective potential against ischemic brain injury and diabetic encephalopathy. However, the therapeutic impact of GXNT on post-IS functional outcomes and pathological injury, as well as the underlying molecular mechanisms and anti-IS active substances, remain unclear.Methods: To answer the above questions, neurological and behavioral assessment, cerebral lesions, and blood-brain barrier (BBB) integrity were combined to comprehensively investigate GXNT's pharmacodynamic effects against post-IS injury. The possible molecular mechanisms were revealed through transcriptome sequencing coupled with experimental verification. Furthermore, the brain tissue distribution of main components in GXNT, behavioral changes of IS zebrafish, and molecular docking were integrated to identify the anti-IS active compounds.Results: Treatment with GXNT significantly mitigated the functional deficits, cerebral cortex lesions, and BBB disruption following IS. Transcriptome sequencing and bioinformatics analysis suggested that complement and coagulation cascades as well as inflammation might play crucial roles in the GXNT's therapeutic effects. Molecular biology experiments indicated that GXNT administration effectively normalized the abnormal expression of mRNA and protein levels of key targets related to complement and coagulation cascades (eg C3 and F7) and inflammation (eg MMP3 and MMP9) in the impaired cortical samples of IS mice. The locomotor promotion in IS zebrafish as well as favorable affinity with key proteins (C3, F7, and MMP9) highlighted anti-IS activities of brain-permeating constituents (senkyunolide I and protocatechuic acid) of GXNT.Conclusion: Taken together, these intriguing findings indicate that GXNT intervention exerts a beneficial effect against post-IS injury via regulating the complement and coagulation cascades pathway and mobilizing inflammatory network. Senkyunolide I and protocatechuic acid show promise as anti-IS active compounds. Keywords: Guanxinning tablet, post-ischemic stroke injury, complement and coagulation cascades, inflammatory network mobilization, active substance